The Effect of Zakat on Poverty in Aceh Province: The Role of Employment Opportunity as a Moderating Variable - Nataja, Saufa Yarda; Yusuf, Muhammad Yasir; Amri, Khairul (Yayasan Kawanad, 2025)
This study analyzes the impact of zakat and employment opportunities on poverty as well as the moderating role of employment opportunities in the zakat-poverty relationship. Using panel data regression with Eviews, the findings show differences between the baseline model and the interaction model. In the basic model, zakat and employment opportunities have a negative and significant effect on poverty. However, in the interaction model, both variables are insignificant, and the moderating effect of employment opportunities is also insignificant (P-value 0.2887). This result shows that employment opportunity does not strengthen or weaken the relationship between zakat and poverty reduction. This may be due to the distribution of zakat that is not well-targeted or consumptive, as well as unequal or low-quality employment opportunities. To increase the role of zakat in poverty alleviation, strategic steps are needed such as more productive distribution of zakat, skills training, and increasing access to decent work